Gut microbiota metabolites and key target molecules in allergic rhinitis: a multi-omics study of gut-nose axis regulation via the inflammation-metabolism network - Zhang, Jingqi; Zhao, Mengqi; Yu, Ya; Zeng, Yining; Sun, Meiyi; Wu, Chuanyu; Guo, Tao; Lin, Liping; Liu, Zhiqing; Xie, Hui (Frontiers in Microbiology, 2025)
IntroductionAllergic rhinitis (AR) is a globally prevalent immune-mediated disorder. While the “gut-nasal axis” suggests that gut microbiota metabolites can modulate AR, the specific molecular networks and key targets involved remain poorly defined. This study aimed to systematically explore the molecular connections between gut microbiota-derived metabolites and AR, and to identify potential therapeutic targets.MethodsWe performed an integrative multi-omics analysis using databases including gutMGene and GeneCards to identify overlapping genes. Summary-data-based Mendelian randomization (SMR) was used to investigate associations between genetic variation, DNA methylation, gene expression, and AR. Single-cell analysis was conducted to examine gene expression patterns in the AR nasal mucosa. Finally, upstream analysis, target prediction, and molecular docking were employed to identify key metabolites, protein targets, and candidate drugs.ResultsWe identified 20 overlapping genes, highlighting a significant association between AR and core inflammatory mediators like IL6, TNF, IL1B, and IL4R. SMR analysis indicated that genetic and epigenetic regulation within the interleukin gene family is closely linked to AR. Single-cell analysis revealed distinct expression patterns of these core genes in the nasal mucosa. Upstream analysis connected these findings to specific microbiota-derived metabolites, notably indole-3-propionic acid and succinate. MPO and PTGDR2 were identified as key potential targets, and Fevipiprant and Zileuton were proposed as candidate drugs.ConclusionThis study provides the first systematic exploration of the “gut-nasal” metabolic axis in AR at a multi-level molecular network level, offering novel perspectives on the disease's underlying mechanisms. The identified targets and candidate drugs provide a valuable foundation for developing new therapeutic strategies, warranting further experimental validation for potential clinical translation.